2017
DOI: 10.17235/reed.2017.4593/2016
|View full text |Cite
|
Sign up to set email alerts
|

Waldmann’s disease: a rare cause of protein losing enteropathy in an adult patient

Abstract: Primary intestinal lymphangiectasia or Waldmann's disease is an uncommon cause of protein losing enteropathy with an unknown etiology and is usually diagnosed during childhood. It is characterized by dilation and leakage of intestinal lymph vessels leading to hypoalbuminemia, hypogammaglobulinemia and lymphopenia. Differential diagnosis should include erosive and nonerosive gastrointestinal disorders, conditions involving mesenteric lymphatic obstruction and cardiovascular disorders that increase central venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 10 publications
(8 reference statements)
0
31
0
Order By: Relevance
“…Along with above clinical features , Stool analysis may show steatorrhea and increased α anti trypsin clearance (>24 ml/day) . (2,8,11) PIL diagnosis is confirmed by the presence of intestinal lymphangiectasia based on endoscopic findings with the corresponding histology of intestinal biopsy specimens. (12) .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Along with above clinical features , Stool analysis may show steatorrhea and increased α anti trypsin clearance (>24 ml/day) . (2,8,11) PIL diagnosis is confirmed by the presence of intestinal lymphangiectasia based on endoscopic findings with the corresponding histology of intestinal biopsy specimens. (12) .…”
Section: Discussionmentioning
confidence: 96%
“…(6,7) Although most cases are sporadic, Le Bougeant et al reported rare familial forms of Waldmann's disease. (8,9) Primary and secondary, are the two types of intestinal lymphangiectasia described in literature according to cause of the disease. In primary lymphangiectasia, there is no predisposing condition to increased lymph pressure and is probably caused by congenital anatomical malformation of the lymphatic system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations